An Improved Power-Sharing Method for a Multi-Terminal HVDC Transmission System Based on Adaptive Voltage Droop Control - Liuming Jing; Jiahe Wei; Lei Xia; Zhaolin Fan; Jinghua Zhou (Energies, 2023)
The prerequisite for the normal operation of a flexible high-voltage direct current (HVDC) transmission system is the maintenance of the stability of the direct current (DC)-side voltage, and droop control has a good dynamic regulation capability. In this paper, we first study the operating characteristics of droop control and derive its equivalent circuit, as well as the power distribution equation for droop control with a four-terminal system as an example. Then, based on this, an improved droop control method is proposed so that the droop factor can be adaptively adjusted according to the power change and provide corresponding characteristics under different operating conditions to enhance the power regulation capability of the controller under high power fluctuations. Finally, a power systems computer-aided design (PSCAD) electromagnetic transient model of the four-terminal, flexible, high-voltage DC transmission system was established and verified by simulation results.